EFFECT OF FEED (Tubifex sp) AND WATER DEBIT ON GROWTH AND CELULUSHIDUPUP OF SELF-FISH LARVA (Ompok rhadinurus) - Obiyan Syahputra; Hamdan Alawi; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT             The study was conducted on 11 July - 20 August 2018 in the Laboratory of Fish Breeding and Breeding at the Faculty of Fisheries and Marine Sciences, University of Riau, Pekanbaru. The purpose of this study was to determine the effect of the type % Tubifex (fresh, frozen and dry) and water change rate (L / minute) (debit) on the growth and survival of sheat fish larvae (Ompok rhadinurus) feed in recirculation system for 40 days. The method used is a Factorial Complete Random Match (RAL) with two factors, namely the first factor in the form of feed with three levels each Tubifex fresh (Ts), frozen Tubifex (Tb), dry Tubifex (Tk). While the second factor is the water debit of each D1 (1 liter / minute water debit), D0.5 (0.5 liter / minute water discharge). To minimize errors, each level of treatment was repeated 3 times. The best growth rate in the treatment of Ts D1 (Tubifex fresh with 1 liter / minute water discharge) with an absolute weight of 7.85 gr, absolute length 10.11 cm, average growth rate of 18.23% / day, and survival rate 94.44. The condition of water quality is the water temperature 27-280C, pH 5,6-5,7 and dissolved oxygen 5,6-6,1 mg / l. Keywords : Ompok rhadinurus, Type %, Tubifek sp, water